ASSESSMENT OF SOIL EROSION IN THE DRAINAGE BASIN OF PEQUENO RIVER, PARATY MUNICIPALITY, RIO DE JANEIRO STATE - Santos, Rafael Carvalho; Guerra, Antonio Jose Teixeira (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1060, 2021)
Soil erosion is a natural phenomenon that has been accelerated by inadequately human activities, resulting in soil degradation and its multiple functions. In this sense, the objective of this research work is to assess the environmental status of the drainage basin of Pequeno river, Paraty Municipality, Rio de Janeiro State, with emphasis on soil erosion. The methodological procedures involved bibliographical and documentary surveys, fieldwork, analysis of soil attributes and thematic mappings. The results show that the relief characteristics contribute to geomorphological processes acceleration and, despite the limitations, soils showed low erodibility. However, changes in vegetation cover and inadequate use and management have an influence on the supply of organic matter into the soil, which may affect its attributes and increase its erodibility over time.